Carta de Roberto H. Todd a Rafael Martínez Nadal - Todd, Roberto H.; Martínez Nadal, Rafael (My University, 1924)
Diversas gestiones del Partido Republicano en New York.
Keywords: Partido Republicano (Puerto Rico); Republican party. Puerto Rico.; Barceló, Antonio R., 1868-1938; Tous Soto, José, 1874-1933